2010
DOI: 10.1504/ijtel.2010.031262
|View full text |Cite
|
Sign up to set email alerts
|

Extending a virtual chemistry laboratory with a collaboration script to promote conceptual learning

Abstract: We developed collaborative extensions to 'Vlab', a web-based laboratory that supports students in conducting virtual chemistry experiments. While results from a recent study indicated that VLab promotes chemistry learning, they also revealed that there is room for improvement. We embedded VLab into a collaborative environment that implements a computer-supported collaboration script for guiding students through the stages of scientific experimentation. We describe our pedagogical approach, our collaboration sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 25 publications
0
39
0
1
Order By: Relevance
“…Fading is not restricted to one specific pedagogy and has been studied, for example, with regard to collaborative learning (Bouyias and Demetriadis 2012;Tsovaltzi et al 2012;Fischer 2011), inquiry learning (McNeill et al 2006), learning for conceptual change (Biemans and Simons 1996), and worked examples (Renkl and Atkinson 2003;Van Gog and Rummel 2010). Although scientific evidence demonstrates effectiveness of fading for learning in some studies (e.g., Renkl et al 2004;Tsovaltzi et al 2010), results that are mixed (e.g., Leutner 2000;McNeill et al 2006) and even disappointing (e.g., Bouyias and Demetriadis 2012;Wecker et al 2010) are reported as well. In the following section, we explain these inconclusive results for various fading instructional scaffolds in CABLe situations.…”
Section: Adaptive Fading Of the External Supportmentioning
confidence: 99%
See 4 more Smart Citations
“…Fading is not restricted to one specific pedagogy and has been studied, for example, with regard to collaborative learning (Bouyias and Demetriadis 2012;Tsovaltzi et al 2012;Fischer 2011), inquiry learning (McNeill et al 2006), learning for conceptual change (Biemans and Simons 1996), and worked examples (Renkl and Atkinson 2003;Van Gog and Rummel 2010). Although scientific evidence demonstrates effectiveness of fading for learning in some studies (e.g., Renkl et al 2004;Tsovaltzi et al 2010), results that are mixed (e.g., Leutner 2000;McNeill et al 2006) and even disappointing (e.g., Bouyias and Demetriadis 2012;Wecker et al 2010) are reported as well. In the following section, we explain these inconclusive results for various fading instructional scaffolds in CABLe situations.…”
Section: Adaptive Fading Of the External Supportmentioning
confidence: 99%
“…The most prominent recent approach is the use of adaptive fading (e.g., Kumar et al 2007;Tsovaltzi et al 2010;Vogel et al 2015). When the continuous application of a strategy (as suggested by external instructional support) is guaranteed, adaptation and adjustment of the strategy through fading is necessary for internalization of the external script and enhancement of the internal script development.…”
Section: Adaptive Fading Of the External Supportmentioning
confidence: 99%
See 3 more Smart Citations